Maximum inferior vena cava diameter predicts post-induction hypotension in hypertensive patients undergoing non-cardiac surgery under general anesthesia: A prospective cohort study - Zhang, Hanying; Gao, Hongguang; Xiang, Yuanjun; Li, Junxiang (Frontiers in Cardiovascular Medicine, 2022)
Background Inferior vena cava (IVC) ultrasonography is a reliable variable that predicts post-induction hypotension (PIH) in patients undergoing surgery under general anesthesia. However, in patients with hypertension, the predictive performance of ultrasound IVC measurements needs further exploration. Methods This is a prospective cohort study. Adult patients with existing hypertension scheduled to undergo non-cardiac surgery under general anesthesia were eligible. An abdominal ultrasound examination was conducted immediately prior to anesthesia induction (0.03 mg kg–1 midazolam, 0.3 mg kg–1 etomidate, 0.4 μg kg–1 sufentanil, and 0.6 mg kg–1 rocuronium). IVC collapsibility index (IVC-CI) was calculated as (dIVCmax–dIVCmin)/dIVCmax, where dIVCmax and dIVCmin represent the maximum and minimum IVC diameters at the end of expiration and inspiration, respectively. PIH was defined as a reduction of mean arterial pressure (MAP) by >30% of the baseline or to <60 mmHg within 10 min after endotracheal intubation. The diagnostic performance of IVC-CI, dIVCmax, and dIVCmin in predicting PIH was also examined in a group of normotensive patients receiving non-cardiac surgery under the same anesthesia protocol. Results A total of 51 hypertensive patients (61 ± 13 years of age, 31 women) and 52 normotensive patients (42 ± 13 years of age, 35 women) were included in the final analysis. PIH occurred in 33 (64.7%) hypertensive patients and 19 (36.5%) normotensive patients. In normotensive patients, the area under the receiver operating curve (AUC) in predicting PIH was 0.896 (95% confidence interval [CI]: 0.804–0.987) for IVC-CI, 0.770 (95% CI: 0.633–0.908) for dIVCmax, and 0.868 (95% CI: 0.773–0.963) for dIVCmin. In hypertensive patients, the AUC in predicting PIH was 0.523 (95% CI: 0.354–0.691) for IVC-CI, 0.752 (95% CI: 0.621–0.883) for dIVCmax, and 0.715 (95% CI: 0.571–0.858) for dIVCmin. At the optimal cutoff (1.24 cm), dIVCmax had 54.5% (18/33) sensitivity and 94.4% (17/18) specificity. Conclusion In hypertensive patients, IVC-CI is unsuitable for predicting PIH, and dIVCmax is an alternative measure with promising performance. Clinical trial registration [http://www.chictr.org.cn/], identifier [ChiCTR2000034853].